Ensemble based machine learning approach for prediction of glioma and multi-grade classification. (October 2021) - Chandra Joshi, Rakesh; Mishra, Rashmi; Gandhi, Puneet; Pathak, Vinay Kumar; Burget, Radim; Dutta, Malay Kishore
Abstract: Glioma is the most pernicious cancer of the nervous system, with histological grade influencing the survival of patients. Despite many studies on the multimodal treatment approach, survival time remains brief. In this study, a novel two-stage ensemble of an ensemble-type machine learning-based predictive framework for glioma detection and its histograde classification is proposed. In the proposed framework, five characteristics belonging to 135 subjects were considered: human telomerase reverse transcriptase (hTERT), chitinase-like protein (YKL-40), interleukin 6 (IL-6), tissue inhibitor of metalloproteinase-1 (TIMP-1) and neutrophil/lymphocyte ratio (NLR). These characteristics were examined using distinctive ensemble-based machine learning classifiers and combination strategies to develop a computer-aided diagnostic system for the non-invasive prediction of glioma cases and their grade. In the first stage, the analysis was conducted to classify glioma cases and control subjects. Machine learning approaches were applied in the second stage to classify the recognised glioma cases into three grades, from grade II, which has a good prognosis, to grade IV, which is also known as glioblastoma. All experiments were evaluated with a five-fold cross-validation method, and the classification results were analysed using different statistical parameters. The proposed approach obtained a high value of accuracy and other statistical parameters compared with other state-of-the-art machine learning classifiers. Therefore, the proposed framework can be utilised for designing other intervention strategies for the prediction of glioma cases and their grades. Graphical abstract: Image 1 Highlights: The proposed machine-learning-based glioma recognition and multi-grade glioma classification framework is a two-stage system. After the histopathological analysis and clinical testing, data were generated for both control and glioma subject groups. A five-fold cross-validation method is used and experimental results were analysed in different statistical parameters. The proposed approach achieved a high value of accuracy and other performance parameters. The risk factor analysed in this study can be taken as a biomarker in developing a glioma diagnosis system.